Acceptability Study of A3-K3 Robotic Architecture for a Neurorobotics Painting - Tramonte, Salvatore; Sorbello, Rosario; Guger, Christopher; Chella, Antonio (Frontiers in Neurorobotics, 2019)
In this paper, authors present a novel architecture for controlling an industrial robot via Brain Computer Interface. The robot used is a Series 2000 KR 210-2. The robotic arm was fitted with DI drawing devices that clamp, hold and manipulate various artistic media like brushes, pencils, pens. User selected a high-level task, for instance a shape or movement, using a human machine interface and the translation in robot movement was entirely demand to the Robot Control Architecture defining a plan to accomplish user’s task. The architecture was composed by a Human Machine Interface based on P300 Brain Computer Interface and a robotic architecture composed by a deliberative layer and a reactive layer to translate user’s high-level command in a stream of movement12for robots joints. To create a real-case scenario, the architecture was presented at Ars Electronica Festival, where the A3-K3 architecture has been used for painting. Visitors14completed a survey to address 4 self-assessed different dimensions related to human-15robot interaction: the technology knowledge, the personal attitude, the innovativeness16and the satisfaction. The obtained results have led to further exploring the border of human-robot interaction, highlighting the possibilities of human expression in the18interaction process with a machine to create art